Aplikasi Pupuk Organik Cair Urin Sapi Terhadap Pertumbuhan dan Produksi Kacang Hijau (Vigna radiata L.) - M. Darmawan (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2017)
Mung bean was a commodity that is widely consumed and has a high nutrient, while the production of mung bean in Indonesia is not stable. One influencing factor is the lack of available nutrients for growth and mung bean production. Cow urine is one type of liquid organic fertilizer derived from cow dung. Generally, cow urine contains elements of N, P and K are high enough and can improve plant resistance. The aim of this research was to know the effect of cow urine as organic fertilizer to mung bean growth and production. This research was carried out in January until March 2016 at Toto Utara Village, Kabila District, Bone Bolango Regency, Gorontalo Province. The study was prepared using Group Randomized Design (GRD) consisting of four treatments and four replications so that there were 16 experimental units.The treatment was different doses of organic fertilizer from cow urine, i.e P0 (control), P1 (50 ml / l of water or 30 l / ha), P2 (150 ml / l water or 90 l / ha), P3 (250 ml / l water or 150 l / ha). The result of the research showed that P3 (150 l/ha) on plant height, the number of the leaf, the number of pods and the weight of seeds.